Transformational spaces: educators discuss map the system and supporting Canada’s emerging generation of systems thinkers - McGowan, Katharine; Calf Robe, Latasha; Allan, Laura; Bray-Collins, Elinor Flora; Couture, Mathieu; Croft, Sarah; Daling, Antonio; Farahbakhsh, Amy; Grossman, Susan; Hassan, Sara; Heidebrecht, Paul; Helwig, Nicole; et al. (Social Enterprise Journal, 2021)
The purpose of this paper is to explore multiple Canadian educators' experiences with the Map the System (MTS) competition, designed to foster and grow systems thinking capacity among students exploring complex questions. The challenge has been an opportunity for social innovation programs (from the nascent to the established) across Canadian post-secondaries to engage both with their own communities and with social innovators internationally, connecting social innovation spaces as part of their third mission. Across the organizations, students valued the interdisciplinary and systems thinking qualities, and organizations benefited from the external competition, there remain questions about organizational engagement in social innovation as a deeply transformative process internally. Design/methodology/approach All Canadian post-secondary institutions who participated in the 2020 MTS competition (17) were invited to a digital roundtable to discuss their experiences. Ten were able to participate, representing a range of post-secondaries (including large research institutions, undergraduate-only universities and colleges). To facilitate discussion, participants met to discuss format and topics; for the roundtable itself, participant educators used a google form to capture their experiences. These were summarized, anonymized and redistributed for validation and clarification. To reflect this collaborative approach, all participant educators are listed as authors on this paper, alphabetically after the organizing authors. Findings For students participating in MTS, they have built both their interdisciplinary and systems thinking skills, as well as their commitment to achieving meaningful change in their community. But MTS arrived in fertile environments and acted as an accelerant, driving attention, validation and connection. Yet while this might align with post-secondary education’s third mission, educators expressed concerns about sustainability, internal commitment to change and navigating tensions between a challenge approach and collaborative work, and internal work and national competition limitations. This complicates the simple insertion of MTS in a post-secondary’s social innovation-related third mission. Research limitations/implications This study was limited to Canadian post-secondaries participating in MTS, and therefore are not representative of either post-secondaries in Canada, or all the MTS participants although Canada is well represented in the challenge itself. Additionally, while the authors believe their approach to treat all participants as authors, and ensured multiple feedback opportunities in private and collectively, this is a deliberate and potentially controversial move away from a traditional study. Social implications More than half of Canadian universities (a subgroup of post-secondaries) had at least one social innovation initiative, but questions have been raised about whether these initiatives are being evaluated internally, or are triggering the kinds of transformative internal work that might be an outcome. Understanding the impact of MTS one example of a social innovation-related initiative can help advance the broader conversation about the place (s) for social innovation in the post-secondary landscape – and where there is still significant work to be done. Originality/value As Canada has only participated in MTS for four years, this is the first inter-institution consideration of its related opportunities and obstacles as a vehicle for transformational social innovation. As well, educators talking openly and frankly to educators reinforces the collaborative quality of social innovation across the post-secondary landscape.
Keywords: Canada